2014
DOI: 10.1016/j.fuel.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the gasification kinetics of a single wood char particle from a limited set of parameters

Abstract: . Prediction of the gasification kinetics of a single wood char particle from a limited set of parameters. Fuel, Elsevier, 2014, 123, pp.194-204 Three functions were built to calculate particle conversion rate of steam gasification, Boudouard reaction and combustion. Function determination includes the use of a validated particle model and a numerical experimental design. The functions take into account all phenomena controlling particle conversion rate of a char particle under a reactive atmosphere.The functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…are determined by vi=ωi Cc,0 where C c,0 is the initial concentration of char and the notation ω i denotes the char conversion rate for each heterogeneous reaction (1)–(3). These char conversion rates have been correlated by Teixeira and coworkers to the experimental parameters, temperature T and partial pressure of the reactant gas P j ( i .e., H 2 O, CO 2 , and O 2 ), as well as the char properties, porosity ε p , particle thickness e p and reaction pre‐exponential factor A i , by three functions that take the form log10ωi=ftrue(T,Pj,enormalp, εnormalp, Aitrue) …”
Section: Modeling Approachmentioning
confidence: 99%
“…are determined by vi=ωi Cc,0 where C c,0 is the initial concentration of char and the notation ω i denotes the char conversion rate for each heterogeneous reaction (1)–(3). These char conversion rates have been correlated by Teixeira and coworkers to the experimental parameters, temperature T and partial pressure of the reactant gas P j ( i .e., H 2 O, CO 2 , and O 2 ), as well as the char properties, porosity ε p , particle thickness e p and reaction pre‐exponential factor A i , by three functions that take the form log10ωi=ftrue(T,Pj,enormalp, εnormalp, Aitrue) …”
Section: Modeling Approachmentioning
confidence: 99%
“…Compared to empirical modelling approaches based on the mathematical fitting of the results [7], the developed model owns a certain physical meaning.…”
Section: Introductionmentioning
confidence: 99%
“…The char conversion rate can be modelled by empirical laws fitted on the mass loss of the solid (Diblasi, 2008;Laurendeau, 1978;Teixeira et al, 2014) but the most advanced models are rather based on the fundamental parameters which control the reactivity of char, namely: the carbon active sites and surface chemistry of char (Bar-Ziv and Kantorovich, 2001;Campbell and Mitchell, 2008;Davis et al, 1995;Geier et al, 2013;Gupta and Bhatia, 2000;Hurt and Calo, 2001;Hurt and Haynes, 2005;Klose and Wölki, 2005;Leistner et al, 2012;Lizzio et al, 1990;Radović et al, 1983), the accessible surface area and porous structure of the particle (Ballal and Zygourakis, Extensive models have emphasized the importance of structural effects on the conversion rate especially for microporous char (Ballal and Zygourakis, 1987;Bhatia and Perlmutter, 1980;Bhatia and Vartak, 1996;Gavalas, 1980;Kantorovich and Bar-Ziv, 1994). It has been shown that the surface chemistry is also a very important parameter and should be considered with the porous structure for a proper modelling of char oxidation (Bar-Ziv and Kantorovich, 2001;Gupta and Bhatia, 2000;Kantorovich and Bar-Ziv, 1994;Leistner et al, 2012;Ma and Mitchell, 2009;Miura et al, 1989;Yaşyerli̇et al, 1996).…”
Section: Introductionmentioning
confidence: 99%